Privacidade digital das instituições bancárias - Ribeiro, Cinthya Imano Vicente (2020)
This dissertation deals with the evolution of the concept of privacy in relation to the General Data Protection Regulation and how this law is to influence the behavior of data subjects, especially bank data and how banks may act in this new scenario. Firstly, we will deal with the internet and how it has evolved in a short time and the ease it has brought to our daily lives, thus changing the concept of privacy. In the previous decade, privacy was preserved as something extremely intimate and, today, it is difficult to talk about preservation, but rather a wide exposure of privacy, because everything is shown and shared and even a phenomenon of exaltation to the lack of privacy. Such phenomenon happens because as far as more people know about each other, the better services most companies are able to provide to their customers, since the more the market knows about our data, the better service and offers they can deliver. Within this realm, the General Data Protection Regulation demonstrates the care to keep data, whether personal or sensitive, preserved and the concerns that the owners should have when exposing it, giving consent to use, sharing such information. The importance they have acquired for business and especially for the banking sector and the new Open Banking system that may be in place in the second half of 2020, as well as all the information that is shared and the responsibility that will be charged to them in a concrete scenario